The Effect of Giving Coconut Oil Scrub with Lime Water to Reducing Body Temperature in Toddler with Fever - Ustifina Hasanah Hasibuan; Debby Pratiwi; Dhea Layla Syahfitri (Indonesian Journal of Global Health Research, 2025)
Fever or febrile is a condition where the body temperature bocems higher, and this is a symptom of disease. This fever occurs due to the normal response to infections in the body, infections that occur due to microorganisms that enter the body, which are viruses, fungi, parasites and bacteria. Giving coconut oil scrub with lime water is believed to help reduce fever in toddlers. Objective to determine the effect of giving coconut oil scrub with lime water on reducing body temperature in toddlers with fever. This research is a type of experimental research. The research population is a toddler with a high body temperature of 35 people at the Nining Clinic in 2024. The sample in this study was 30 toddlers with high body temperature using purposive sampling. The Body Temperature Measurement Procedure uses a thermometer in axillary 3 times before treatment, directly after treatment, and 30 minutes after treatment. Data analysis using t paired sample test. Research shows that the average temperature measurement of toddlers is 38.77 degrees Celsius (fever). While the average temperature after giving coconut oil and lime scrub was 37.30 degrees Celsius with a normal temperature of 21 (70%) and 9 people had fever (30%). The result of the paired sample test is calculated by 11,897 with a value of p=0.000 (p<0,05). This means that there is a significant difference between the temperature before the treatment of coconut oil only scrub and coconut oil and lime scrub. This result proves that giving coconut oil body scrub with lime water has a positive effect on lowering body temperature in toddlers with fever at the Nining Clinic in 2024. There is a significant effect of giving coconut oil scrub with lime water on the decrease in body temperature in toddlers with fever at the Nining Clinic in 2024.